Seek to see him : ascent and vision mysticism in the Gospel of Thomas - De Conick, April D. (Vigiliae Christianae, Supplements, 1996)
This monograph represents a critical juncture in Thomas studies since it dispels the belief that the Gospel of Thomas originates from gnostic traditions. Rather, Jewish mystical and Hermetic origins are proposed and examined. Following this analysis, the anthropogony and soteriology of Thomas are discussed. The Thomasites taught that they were the elect children of the Father, originating from the Light. The human, however, became unworthy of these luminous beginnings and was separated from the divine when Adam sinned. Now he must purify himself by leading an encratite lifestyle. He is to ascend into heaven, seeking a visio dei which will transform him into his original immortal state and grant him citizenship in the Kingdom.